1987
DOI: 10.1002/j.1460-2075.1987.tb02355.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of human secretogranin I (chromogranin B): comparison with chromogranin A reveals homologous terminal domains and a large intervening variable region.

Abstract: Communicated by B.DobbersteinWe have determined and analyzed the primary structure of human secretogranin I (chromogranin B), a tyrosine-sulfated secretory protein found in a wide variety of peptidergic endocrine cells. A 2.5-kb cDNA clone, hybridizing to an mRNA of similar length, was isolated from a cDNA library of human pheochromocytoma. The identity of the clone was established by comparison of its deduced amino acid sequence with N-terminal and several internal secretogranin I sequences as well as by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(126 citation statements)
references
References 46 publications
4
122
0
Order By: Relevance
“…21,22 The CHGB gene encodes for chromogranin B, which belongs to a family of soluble proteins stored and released from large dense-core secretory vesicles at the synapse. 36,37 These granins have an important role in the sorting and aggregation of secretory products in the transGolgi network and in the subsequent formation of secretory granules. 38 A reduction of chromogranin B levels in cerebrospinal fluid (CSF), as well as chromogranin B-like immunoreactivity in distinct subregions of the hippocampus were reported in patients with SZ.…”
Section: Synapse and Neurotransmissionmentioning
confidence: 99%
“…21,22 The CHGB gene encodes for chromogranin B, which belongs to a family of soluble proteins stored and released from large dense-core secretory vesicles at the synapse. 36,37 These granins have an important role in the sorting and aggregation of secretory products in the transGolgi network and in the subsequent formation of secretory granules. 38 A reduction of chromogranin B levels in cerebrospinal fluid (CSF), as well as chromogranin B-like immunoreactivity in distinct subregions of the hippocampus were reported in patients with SZ.…”
Section: Synapse and Neurotransmissionmentioning
confidence: 99%
“…Since there are only two cysteine residues in the entire CGA molecule and these two cysteines are located in the 17th and 38th positions from the N-terminus [17,18], formation of the compact N-terminal core structure may owe its existence to a disulfide bond formed between the two cysteines [19]. In our previous studies, it was shown that chromogranin A bound more Ca" at pH 5.5 than at pH 7.5, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the same antibody also reacted with a protein of -110 kDa in several of these tissues. However, the identity of the band is not clear at present although chromogranin B [15], another member of the chromogranin family, has a size of -110 kDa on the SDS-gel and has previously been shown to crossreact with a chromogranin A antibody [ 161. In parallel experiments, an identical protein blot was also immunoreacted with the monoclonal antibody.…”
Section: Febs Letters February 1993mentioning
confidence: 99%